A consistent description of intermetallic particle composition: An analysis of ten batches of AA2024‐T3. (21st January 2013) - Hughes, A. E.; Glenn, A. M.; Wilson, N.; Moffatt, A.; Morton, A. J.; Buchheit, R. G.
<x xml:space="preserve">Abstract</x> Advances in electron microprobe analyses have made it possible to characterise large areas at very fine pixel size relatively quickly. In a recent study by some of the authors, a 2 × 2 mm2 area of AA2024‐T351 was mapped using a step size of approximately 0.4 µm. Both wavelength dispersive intensities as well as energy dispersive spectra were collected at each pixel thus forming a hyperspectral dataset. That study revealed a number of compositions within the AA2024‐T351, distributed as either individual particles or compositional domains within particles. In the current study, ten batches of sheet product were examined. Nine batches of relatively new product had a common set of compositions for the different particles types in the different batches, but exhibited variation in the number density of the different types of particles. An older batch, however, had a completely different profile of compositions for the particles. The compositions of intermetallic particles in newer batches did not match what would be considered textbook compositions, raising the possibility that improved processing and purity of new AA2024‐T351 might lead to different particle types to those considered to be typical for AA2024‐T351 sheet. Copyright © 2013 John Wiley & Sons, Ltd.